Repeated intravenous administration of silica nanoparticles induces pulmonary inflammation and collagen accumulation via JAK2/STAT3 and TGF-β/Smad3 pathways in vivo - Yu Y (Dove Medical Press, 2019)
Yang Yu1,2, Tingting Zhu1, Yang Li1,2, Li Jing1,2, Man Yang1,2, Yanbo Li1,2, Junchao Duan1,2, Zhiwei Sun1,2 1Department of Toxicology and Sanitary Chemistry, School of Public Health, Capital Medical University, Beijing, People’s Republic of China; 2Beijing Key Laboratory of Environmental Toxicology, Capital Medical University, Beijing, People’s Republic of ChinaCorrespondence: Zhiwei Sun; Junchao DuanDepartment of Toxicology and Sanitary Chemistry, School of Public Health, Capital Medical University, Beijing 100069, People’s Republic of ChinaTel +86 01 08 391 1507; +86 01 08 391 1868Email zwsun@ccmu.edu.cn; jcduan@ccmu.edu.cnBackground: The health hazards of silica nanoparticle (SiNP) are raising worldwide concern as SiNPs has become the second largest manufactured nanomaterial in global markets. However, insufficient data for the adverse health effects and safety evaluation of SiNPs are remaining a big question.Purpose: We evaluated the effects and related mechanism of SiNPs on pulmonary inflammation and collagen production through repeated intravenous administration in mice in a 45-day observation period.Methods: Morphological and ultrastructural change, ultradistribution of SiNPs in lungs were observed in ICR mice through intravenous administration. Oxidative damage, pro-inflammatory cytokines, hydroxyproline content, the marker of fibroblasts and epithelial-mesenchymal transition (EMT), and JAK2/STAT3 and TGF-β1/Smad3 signaling pathways were detected to explore the lung injuries and related mechanism.Results: The results showed repeated intravenous exposure of SiNPs increased the weight of lung tissues and destroyed pulmonary histomorphological structure. The increased MDA content, depletion of SOD and GSH-Px in lungs were observed in SiNP-treated mice. The protein expressions of JAK2/STAT3 pathway were upregulated in lungs, and the levels of inflammatory cytokines TNF-α, IL-1β, and IL-6 in serum and lungs were also elevated in SiNPs treated group. The increased hydroxyproline content indicated collagen accumulation in lungs of SiNP-treated mice. Meanwhile, the protein expressions of the marker of myofibroblast (a-SMA), the regulators in connective tissue remodeling (CTGF), TGF-β, and p-Smad3 were all upregulated in lungs. In addition, we found intravenous administration of SiNPs-induced ultrastructural changes in type II alveolar epithelial cells but without downregulation of the protein expression of the key markers of epithelial cells (E-Cadherin).Conclusion: Our results revealed that oxidative stress and inflammation contributed to the collagen accumulation through activation of JAK2/STAT3 and TGF-β/Smad3 pathways. It suggests that pulmonary aberrant inflammation and collagen accumulation induced by nanoparticles should be seriously considered for the safety application in diagnostics or therapeutics.Keywords: Silica nanoparticles, repeated intravenous administration, inflammation, collagen accumulation, JAK2/STAT3 signaling pathway, TGF-β/Smad3 signaling pathway